Edge Version of Harmonic Index and Harmonic Polynomial of Rooted Product Graphs - Muhammad Shoaib Sardar; Rabia Nazir; Sohail Zafar; Zohaib Zahid (Journal of Basic & Applied Sciences, 2018)
In this paper we computed explicit formulas for the edge version of harmonic index and harmonic polynomial of some classes of rooted product of graphs and i-th vertex rooted product of graphs.